2018
DOI: 10.17796/1053-4628-42.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dentists' Appearance Related with Dental Fear and Caries aStatus in 6–12 Years Old Children

Abstract: Anxiety and dental caries were associated; small alterations in a dentist's appearance may reduce dental anxiety among children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 1 publication
1
15
1
4
Order By: Relevance
“…One final observation by the students was the stressful impact of formal healthcare providers’ clothing and the white lab coats on the children. Interestingly, the ‘white coat effect’ has been reported in the literature and studies have shown that a clinician’s appearance is one of the factors that play a role in nonverbal communication within the child–physician relationship, and that casual or colourful and decorated attire is preferred over the traditional white coat in reducing the apprehension and stress levels of the patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…One final observation by the students was the stressful impact of formal healthcare providers’ clothing and the white lab coats on the children. Interestingly, the ‘white coat effect’ has been reported in the literature and studies have shown that a clinician’s appearance is one of the factors that play a role in nonverbal communication within the child–physician relationship, and that casual or colourful and decorated attire is preferred over the traditional white coat in reducing the apprehension and stress levels of the patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos envolvendo a avaliação do medo odontológico tornaram-se mais relevantes, à medida que suas várias consequências passaram a ser melhor compreendidas pela comunidade científica (37). Pesquisas prévias confirmaram que crianças com medo odontológico apresentaram pior condição de saúde bucal (18,28), posto que uma saúde bucal precária aumenta a chance de dor dentária, ou pode resultar em uma experiência odontológica negativa (38), o que pode reforçar a ocorrência do medo odontológico (28). É importante, portanto, que sejam identificados os fatores associados ao medo odontológico, para reduzir as consequências geradas pela condição, adotando-se, para isso, uma abordagem adequada.…”
Section: Discussionunclassified
“…As pesquisas transversais se configuraram no desenho de estudo mais utilizado (1,8,9,12,14,(16)(17)(18)(20)(21)(22)(23)(25)(26)(27)29,30,(32)(33)(34)(35). Esse tipo de estudo possibilita determinar o perfil da doença ou condição, fornece informações que determinarão o planejamento de serviços de saúde e são úteis para gerar hipóteses que podem ser confirmadas por meio de desenhos de estudo mais rigorosos, além de serem menos onerosos e mais rápidos (41).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Thus, by acting on related elements (attitude, general environment, etc) it could be possible to establish an atmosphere of trust in which the concerns of patients would greatly be alleviated. The appearance of the dentist is also be shown to influence the degree of fear in young children . Hence, once again, the need for practitioners to be seriously trained in communication is undisputable.…”
Section: Discussionmentioning
confidence: 99%